Study on flexural behavior of concrete beams reinforced with hybrid high-strength and high-toughness (HSHT) and ordinary steel bars. (15th June 2023) - Zhang, Yang; Xiong, Xueyu; Liang, Yuhang; He, Manchao
Highlights: Flexural behavior of concrete beams reinforced with hybrid HSHT and ordinary steel bars. The concrete beams reinforced with HSHT steel bars can bear higher residual strength and superior crack control ability. Hybrid reinforcement can improve the deformation ability, the service performance o, and the energy absorption capacity. The proposed model can accurately calculate the flexural strength of concrete beams reinforced with HSHT steel bars. Abstract: To study the flexural behavior of high-strength and high-toughness (HSHT) reinforced concrete beams with negative Poisson's ratio and special spiral grooves on the surface, fifteen beams of 250 mm × 450 mm × 3200 mm were designed and manufactured to conduct bending tests. The effects of different parameters, including the reinforcement ratio, compressive strength of concrete, loading mode, the number of HSHT steel bars in hybrid reinforcement, and longitudinal steel bars type, were studied on failure modes, crack patterns, flexural stiffness, flexural strength, ductility, and energy absorption capacity. The load versus mid-span deflection curves for concrete beams reinforced with HSHT steel bars can be divided into five stages. The concrete beams reinforced with HSHT steel bars can also bear higher residual strength (approximately 0.9 Fp ) and exhibit superior crack width control ability. The peak load increases by a maximum of 22.9 % with the reinforcement ratio of HSHT steel bars increasing from 0.86 % to 1.08 %. Hybrid reinforcement can improve the service performance of concrete beams, take full advantage of HSHT steel bars, and increase the energy absorption capacity of beams. Based on strain analysis of cross-section, the flexural strength model of concrete beams reinforced with hybrid reinforcement was proposed by considering the ultimate compression strain. The calculation results show that the proposed model can accurately calculate the flexural strength of concrete beams reinforced with HSHT steel bars.